Caracterization of migration from Venezuela to Colombia and its influence on family reunification - Ruiz-Santacruz, J. Sebastian (2022)
This research characterizes Venezuelan migration to Colombia, according to sex, educational level, work activity and by geographical area of ​​the migrants and the times of household reunification. Based on the results of the Colombian Population and Housing Census 2018 (CNPV-2018), the demographic profile of migrants is analyzed, and the characteristic forms of household reunification of Venezuelans in Colombia are examined based on migration times using estimators. Kaplan-Meier and Cox models are used, which allow us to identify that factors such as age, educational level, year of arrival and economic activity are determinants of said reunification times. The research identified that the increase in migration from Venezuela has been decisive in the recent transition of the structure of the Colombian population according to age and sex, as it is concentrated in intermediate ages and with a differentiated profile in the main cities. Likewise, it was possible to identify that the recent Venezuelan migration pattern can be classified as family-type, with emphasis on productive and reproductive ages, and a high presence of minors, and that the still active ties with spouses, children and, in general, relatives who were pioneers in the migratory process is a factor that plays a fundamental role in the differences in the propensities to migrate by households and their members.